Eosinophilic myocarditis: response to corticosteroids - Simkhada, Rabindra; Khatri, Prabin; Badu, Muna (Journal of Universal College of Medical Sciences, 2015)
Eosinophilia is seen in several of the clinical condition and it affects different system of human body. Eosinophils can infiltrate in heart and causes range of cardiac abnormalities. Heart involvement usually occurs when eosinophil count exceeds 1.5×109/L for at least 6 months. Eosinophilic myocarditis is a rare condition. Few cases have been reported and most of them are from western community. The disease is potentially fatal and mortality is high if not recognized on time. Studies have shown various responses to treatment with corticosteroid and other standard heart failure measures. We present a 35 year male that came with complains of shortness of breath and fatigability. He was diagnosed as esoniphilic myocarditis and treated with corticosteroid and other heart failure measures. The patient showed excellent response to therapy. He became entirely asymptomatic and his cardiac function (ejection fraction) became normal during follow up at 60 days.